INFLUENCE OF FEEDING DIETS ON KETOSIS DISEASE IN DIFFERENT PERIODS OF LIFE IN HIGHLY PRODUCTIVE COWS - Аsatbaeva, G. К.; Kulmagambetova, R. Kh. (Ғылым және білім №1, 2020)
For the successful development of dairy farming in production conditions, there are many factors, one of which is compliance with the feeding diet. If the quality, quantity, and chemical composition are not observed, it leads to significant losses in milk production, the main etiological factor in the development of metabolic diseases, one of which is ketosis. In the conditions of modern animal husbandry, it entails excessive functional tension of all organs and systems of the animal body, biochemical, clinical and morphological changes in various organs and tissues and leads to the final result of the development of a metabolic disorder. We analyzed the feeding ration for high-yielding cows, per head per day, a method for determining the average concentration of exchange energy for productivity and dry matter in different periods of life in high-yielding cows and the average amount of b-betahydroxybutyrate in different periods of life in high-yielding cows. Успешное развитие молочного животноводства в условиях производства, складываются из многих факторов, одним из которых является соблюдение рациона кормления. Несоблюдение качества, количества и химического состава рациона кормления, это основной этиологический фактор развития болезней обмена веществ, одним из которых является кетоз, что влечет за собой значительные убытки производства молока. Условия современного интенсивного ведения животноводства, влечет за собой чрезмерное функциональное напряжение всех органов и систем организма животных, что ведет к биохимическим, клиническим и морфологическим изменениям в различных органах и тканях и в конечном результате способствует развитию расстройства обмена веществ. Мы провели исследования анализа суточного рациона кормления высокопродуктивных коров, с определением средней концентрации обменной энергии и сухого вещества, а также среднее количество содержания b-бетагидроксибутирата в разные периоды жизни
Keywords: скотоводство; рк; молочное скотоводство; рацион кормления; производство молока; кетоз; убытки производства молока; highly productive cows; - metabolic diseases; ketosis; feed; diet